Effect of Interleukin6 (IL-6) and Tumor Necrosis Factor (TNF-Α) on Type 2 Diabetes Patients in Kirkuk City - Ali, Hala Abdullah; Ali (B.S), Hussein Abdulbasit (American Journal of Biology and Natural Sciences, 2024)
This study was conducted on patients with type 2 diabetes in Kirkuk city. The study was conducted from October 2023 to mid-January 2024. 90 blood samples were collected from patients with diabetes. Blood samples were taken after fasting for at least 6 hours. Information about each case was recorded based on a pre-prepared form that included information related to the research topic. The samples were distributed into two groups: the first group included 25 blood samples from infected males and 25 blood samples from infected females. The second group included 20 blood samples from healthy males and 20 blood samples from healthy females. The ages of the samples ranged between 25-50 years. The samples were examined in private laboratories (Popular Work Laboratory and Hajjaj Laboratory) in Kirkuk. The tests were completed in the central laboratory at the College of Pharmacy at Tikrit University. The results of the immune variables showed no significant differences in the concentration of interleukin 6 (IL-6) and tumor necrosis factor (TNF-α) in the serum of diabetic patients compared to the control group. The results of the immune variables showed no significant differences in the concentration of interleukin 6 (IL-6) and tumor necrosis factor (TNF-α) in the serum of diabetic patients, males and females, compared to the control group, males and females. The results of the immune variables showed no significant differences in the concentration of interleukin 6 (IL-6) and tumor necrosis factor (TNF-α) in the serum of diabetic patients, compared to the control group, in the three age groups. This study aimed to identify the effect of type 2 diabetes on some immune variables.